1989
DOI: 10.2307/3869006
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cell Wall-Degrading Enzymes by Aspergillus nidulans: A Model System for Fungal Pathogenesis of Plants

Abstract: The cell wall-degrading enzymes polygalacturonase and pectate lyase have been suggested to be crucial for penetration and colonization of plant tissues by some fungal pathogens. We have found that Aspergillus nidulans (= Emericella nidulans), a saprophytic Ascomycete, produces levels of these enzymes equal to those produced by soft-rotting Erwinia species. Induction of polygacturonase and pectate lyase in A. nidulans requires substrate and is completely repressed by glucose. Surprisingly, inoculation of excise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
2
16
0
1
Order By: Relevance
“…Previous work has shown that the production of extracellular polygalacturonases by Aspergillus niger (30), A. nidulans (31), and Penicillium frequentans (32) is induced by the presence of pectin and repressed by glucose. In addition, the carbon catab- olite repression of the polygalacturonase expression by glucose has been reported to operate at the transcriptional level (30,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the production of extracellular polygalacturonases by Aspergillus niger (30), A. nidulans (31), and Penicillium frequentans (32) is induced by the presence of pectin and repressed by glucose. In addition, the carbon catab- olite repression of the polygalacturonase expression by glucose has been reported to operate at the transcriptional level (30,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Dean and Timberlake () proposed a threshold level of NO is required to switch from asexual development to sexual development in A. nidulans (Dean & Timberlake, ). Supplementing the NO‐releasing compound (diethylenetriamine NONOate: (Z)‐1‐[N‐(2‐aminoethyl)‐N‐(2‐ammonioethyl) amino] diazen‐1‐ium‐1,2‐diolate) reduced conidiation but stimulated the formation of sexual structure cleistothecia in Aspergillus species (Baidya et al, ; Marcos et al, ).…”
Section: No and Fungal Cellular Developmentmentioning
confidence: 99%
“…Its estimated 31-megabase genome (1) with low repetitive DNA content (2), distributed among eight chromosomes, is sufficiently complex to direct multicellular development (3,4). With its sophisticated forward and reverse genetics (5,6), A. nidulans has been used to address fundamental questions in cell and molecular biology (7)(8)(9)(10) and has become a model system for the study of pathogenic and biotechnologically useful relatives (11,12). One of the major questions in genomics is the organization of repeated DNA sequences in a genome because this organization has implications for functional organization of genomes, development, chromosome structure and function, recombination, and genome evolution.…”
mentioning
confidence: 99%